Understanding self-care perceptions and behaviours of community care workers in Cape Town to develop and assess a self-care intervention - Singh, Laura (Department of Psychology, 2026)
Community care workers (CCWs) play a crucial role in supporting disadvantaged populations, yet there is insufficient research on how these demands affect their well-being. Burnout among CCWs can lead to diminished performance, impacting their well-being as well as the well-being of the communities they serve. This study used a multi-stage approach, with an interpretivist and constructivist qualitative lens, to explore the self-care needs of CCWs, develop a self-care intervention, and test the feasibility of this intervention. Community-based participatory research (CBPR) principles were employed throughout the study, conducted within an established community organisation, Outliers. Stage 1 involved interviews with 21 CCW team leaders and revealed six key themes that helped understand self-care behaviours and perceptions in CCWs: the demanding nature of community work, attitudinal and practical barriers to self-care, the importance of a personal understanding of self-care, and the need for routine and community support in establishing self-care habits. Based on these findings, a two-session WhatsApp group intervention was designed in collaboration with the team leaders. In Stage 2, the intervention was delivered to 16 CCWs from three organisations. Two post-intervention focus groups with 10 participants reported increased self-awareness, shifts in attitudinal barriers, changes in self-care behaviours, and several barriers to adopting self- care. The use of WhatsApp found to be effective for facilitating training, reflection, and peer support. The findings of this research support the potential of co-designed, community-based participatory approaches to create culturally relevant and impactful interventions for CCWs.